2017
DOI: 10.1177/1357633x17719395
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-based tele-electrocardiography support for primary care physicians reduces the pain-to-treatment time in acute coronary syndrome

Abstract: Background The Himachal Pradesh state acute coronary syndrome registry recorded a median delay of 13 h between the time of onset of pain to the time of making the diagnosis and giving treatment for acute coronary syndrome. We conducted a pilot study on providing 24-h tele-electrocardiography (Tele-ECG) services in the district Kangra of Himachal Pradesh, with the aim to reduce the time taken for diagnosis of acute coronary syndrome. Methods The intervention group for the study included eight rural community he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
(14 reference statements)
1
21
0
Order By: Relevance
“…Based on semi-structured interviews with 22 stakeholders, the study after viewing prototypes found that the benefits of the App outweighed the current paper-based workflow in the management of STEMI patients. The expected benefits included timing accuracy, better communication, improved and faster management, and improvements in data quality, which are in accordance with similar studies [ 32 , 33 ] . These findings were not surprising because the current workflow is based on a paper-based protocol that can be easily lost or contain inaccuracies, and the current code activation depends on the consecutive calling of all team members, which is also time-consuming.…”
Section: Discussionsupporting
confidence: 88%
“…Based on semi-structured interviews with 22 stakeholders, the study after viewing prototypes found that the benefits of the App outweighed the current paper-based workflow in the management of STEMI patients. The expected benefits included timing accuracy, better communication, improved and faster management, and improvements in data quality, which are in accordance with similar studies [ 32 , 33 ] . These findings were not surprising because the current workflow is based on a paper-based protocol that can be easily lost or contain inaccuracies, and the current code activation depends on the consecutive calling of all team members, which is also time-consuming.…”
Section: Discussionsupporting
confidence: 88%
“…Within cardiology, some smartphone applications have become popular in recent years and allowed the publication of data related to their use and viability 6,[10][11][12][13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Other applications are working on the possibility of reducing door-to-balloon time and detect arrhythmias in patients with hypertrophic cardiomyopathy or who suffered an idiopathic stroke 11,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…After review of the titles and abstracts, 167 met the inclusion criteria and after full text review, 28 papers that addressed consent remained. Of the 28 papers, only 11 reported that written consent was obtained of which 5 were for taking photographs [2,6,[11][12][13], and 4 for sharing information with colleagues [2,[14][15][16]. Three papers reported obtaining verbal consent [12,17,18], one of which was for sharing patient information [17].…”
Section: Literature Reviewmentioning
confidence: 99%